2015
DOI: 10.1080/13854046.2015.1087596
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Change in Performance on the Montreal Cognitive Assessment in Older Adults

Abstract: Objective The Montreal Cognitive Assessment (MoCA) is a brief screening measure commonly used to determine cognitive status among older adults. Despite the popularity of the MoCA, there has been little research into how performance on the MoCA changes over time in healthy older adults. Methods The present study examined a sample of older adults (n = 53) recruited for a longitudinal study of healthy aging. Change in total MoCA score at three time-points (baseline, 12 months, and 48 months) and scores from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(91 citation statements)
references
References 36 publications
5
83
3
Order By: Relevance
“…The Montreal Cognitive Assessment was only administered at TP1 because of concerns about a potential learning effect 27. All subjects completed at least 3 of the 4 time points.…”
Section: Methodsmentioning
confidence: 99%
“…The Montreal Cognitive Assessment was only administered at TP1 because of concerns about a potential learning effect 27. All subjects completed at least 3 of the 4 time points.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous research studies have been conducted regarding the ability of the measure to identify cognitive change in individuals with normal cognition (Andreotti & Hawkins, 2015; Cooley et al, 2015; Duff & Ramezani, 2015; Phillips et al, 2015; Thaler, Hill, Duff, Mold, & Scott, 2015), Mild Cognitive Impairment (MCI; Clark, Hobson, & O’Bryant, 2010; Duff, Hobson, Beglinger, & O’Bryant, 2010; Hobson, Hall, Humphreys-Clark, Schrimsher, & O’Bryant, 2010; Karantzoulis, Novitski, Gold, & Randolph, 2013; O’Mahar et al, 2012), and Alzheimer’s disease (AD; Burton, Enright, O’Connell, Lanting, & Morgan, 2015; Duff et al, 2008; Enright, O’Connell, MacKinnon, & Morgan, 2015; Heyanka, Scott, & Adams, 2015; McDermott & DeFilippis, 2010; Morgan, Linck, Scott, Adams, & Mold, 2010; Schmitt et al, 2010). Despite these efforts, however, there have been few studies examining the RBANS and its association with imaging biomarkers related to AD, such as decreased hippocampal volumes on magnetic resonance imaging (MRI; Choi et al, 2016; Jack et al, 2010), hypometabolism on fluoro-2-deoxyglucose (FDG) positron emission tomography (PET; Frings, Spehl, Hull, & Meyer, 2016; Jagust et al, 2010), and amyloid accumulations on amyloid PET (Beach, Thal, Zanette, Smith, & Buckley, 2016; L.…”
Section: Introductionmentioning
confidence: 99%
“…Practice effects have been shown with the MMSE in both healthy adults and those diagnosed with dementia at short test-retest intervals ranging from 10 min to 1.5 weeks (Galasko et al, 1993; Jacqmin-Gadda et al, 1997), and longer intervals of three months (Helkala et al, 2002). Moreover, the MoCA has also demonstrated practice effects in longitudinal performance of healthy older adults (Cooley et al, 2015). The presence of practice effects in cognitive assessments is potentially due to a limited range of questions, and these effects are most prominent on questions evaluating the domains of visual memory, attention, working memory, processing speed, and executive functioning (Cooley et al, 2015).…”
Section: Background Informationmentioning
confidence: 99%
“…Moreover, the MoCA has also demonstrated practice effects in longitudinal performance of healthy older adults (Cooley et al, 2015). The presence of practice effects in cognitive assessments is potentially due to a limited range of questions, and these effects are most prominent on questions evaluating the domains of visual memory, attention, working memory, processing speed, and executive functioning (Cooley et al, 2015). A meta-analysis by Calamia et al (2012) revealed that practice effects are more pronounced with short test-retest intervals.…”
Section: Background Informationmentioning
confidence: 99%